The basics of American politics - Wasserman, Gary (HarperCollins College, 1994)
This book includes case studies of recent events such as the Gulf War; flad burning; computerized "get-out-the-vote" campaigns; the trials of a woman campaigning for the Senate. It is also updated information on the Clinton presidency, Ross Perot, the new Congress, media campaigning, Arthur Ashe and privacy issues, Zoe Baird, and Halary Clinton